Performance Determinants of Public-Sector Employees: The Effects of Education Level, Training, and Job Satisfaction on Employee Performance at the Public Works and Spatial Planning (PUPR) Department of North Sulawesi Province - Deicy Paath; Joulanda A M Rawis; Shelty D.M. Sumual; Jenny Nancy Kaligis; Ruth Umbase (JR Education, 2025)
Employee performance is a strategic issue in public organizations because it directly affects the quality, timeliness, and accountability of public services. In regional government institutions, performance improvement is frequently linked to human resource development efforts especially improving educational qualifications, implementing relevant training, and maintaining job satisfaction. This study investigates the influence of education level, training, and job satisfaction on employee performance at the Public Works and Spatial Planning (PUPRD) Department of North Sulawesi Province. This research employed a quantitative correlational design. The population consisted of 145 employees, while the sample comprised 94 respondents selected through purposive sampling with a minimum tenure criterion of three years. Data were collected using a structured questionnaire and analyzed using descriptive statistics, classical assumption testing, and regression analysis with IBM SPSS. The results indicate that education level, training, and job satisfaction significantly affect employee performance both partially and simultaneously. The multiple regression model obtained was Y = 11.086 + 0.135X₁ + 0.137X₂ + 0.018X₃, where Y is employee performance, X₁ is education level, X₂ is training, and X₃ is job satisfaction. Partial tests showed significant effects for education level (t = 47.089, sig = 0.002), training (t = 50.328, sig = 0.000), and job satisfaction (t = 34.241, sig = 0.003). Simultaneously, the three predictors significantly influenced performance (F = 69.534; sig = 0.001), with Adjusted R² = 0.812, meaning 81.2% of the variance in employee performance was explained by the three variables. The findings suggest that public agencies seeking to strengthen performance should prioritize (1) structured educational development aligned with job demands, (2) equitable access to relevant training programs supported by evaluation, and (3) organizational policies that enhance job satisfaction through work environment improvements, fair compensation perceptions, supervisory support, and clear career pathways.